<< Chapter < Page Chapter >> Page >

Write each of the following products with a single base. Do not simplify further.

  1. ( ( 3 y ) 8 ) 3
  2. ( t 5 ) 7
  3. ( ( g ) 4 ) 4
  1. ( 3 y ) 24
  2. t 35
  3. ( g ) 16
Got questions? Get instant answers now!

Using the zero exponent rule of exponents

Return to the quotient rule. We made the condition that m > n so that the difference m n would never be zero or negative. What would happen if m = n ? In this case, we would use the zero exponent rule of exponents to simplify the expression to 1. To see how this is done, let us begin with an example.

t 8 t 8 = t 8 t 8 = 1

If we were to simplify the original expression using the quotient rule, we would have

t 8 t 8 = t 8 8 = t 0

If we equate the two answers, the result is t 0 = 1. This is true for any nonzero real number, or any variable representing a real number.

a 0 = 1

The sole exception is the expression 0 0 . This appears later in more advanced courses, but for now, we will consider the value to be undefined.

The zero exponent rule of exponents

For any nonzero real number a , the zero exponent rule of exponents states that

a 0 = 1

Using the zero exponent rule

Simplify each expression using the zero exponent rule of exponents.

  1. c 3 c 3
  2. −3 x 5 x 5
  3. ( j 2 k ) 4 ( j 2 k ) ( j 2 k ) 3
  4. 5 ( r s 2 ) 2 ( r s 2 ) 2

Use the zero exponent and other rules to simplify each expression.


  1. c 3 c 3 = c 3 3 = c 0 = 1

  2. −3 x 5 x 5 = −3 x 5 x 5 = −3 x 5 5 = −3 x 0 = −3 1 = −3

  3. ( j 2 k ) 4 ( j 2 k ) ( j 2 k ) 3 = ( j 2 k ) 4 ( j 2 k ) 1 + 3 Use the product rule in the denominator . = ( j 2 k ) 4 ( j 2 k ) 4 Simplify . = ( j 2 k ) 4 4 Use the quotient rule . = ( j 2 k ) 0 Simplify . = 1

  4. 5 ( r s 2 ) 2 ( r s 2 ) 2 = 5 ( r s 2 ) 2 2 Use the quotient rule . = 5 ( r s 2 ) 0 Simplify . = 5 1 Use the zero exponent rule . = 5 Simplify .
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Simplify each expression using the zero exponent rule of exponents.

  1. t 7 t 7
  2. ( d e 2 ) 11 2 ( d e 2 ) 11
  3. w 4 w 2 w 6
  4. t 3 t 4 t 2 t 5
  1. 1
  2. 1 2
  3. 1
  4. 1
Got questions? Get instant answers now!

Using the negative rule of exponents

Another useful result occurs if we relax the condition that m > n in the quotient rule even further. For example, can we simplify h 3 h 5 ? When m < n —that is, where the difference m n is negative—we can use the negative rule of exponents to simplify the expression to its reciprocal.

Divide one exponential expression by another with a larger exponent. Use our example, h 3 h 5 .

h 3 h 5 = h h h h h h h h = h h h h h h h h = 1 h h = 1 h 2

If we were to simplify the original expression using the quotient rule, we would have

h 3 h 5 = h 3 5 =   h −2

Putting the answers together, we have h −2 = 1 h 2 . This is true for any nonzero real number, or any variable representing a nonzero real number.

A factor with a negative exponent becomes the same factor with a positive exponent if it is moved across the fraction bar—from numerator to denominator or vice versa.

a n = 1 a n and a n = 1 a n

We have shown that the exponential expression a n is defined when n is a natural number, 0, or the negative of a natural number. That means that a n is defined for any integer n . Also, the product and quotient rules and all of the rules we will look at soon hold for any integer n .

The negative rule of exponents

For any nonzero real number a and natural number n , the negative rule of exponents states that

a n = 1 a n

Using the negative exponent rule

Write each of the following quotients with a single base. Do not simplify further. Write answers with positive exponents.

  1. θ 3 θ 10
  2. z 2 z z 4
  3. ( −5 t 3 ) 4 ( −5 t 3 ) 8
  1. θ 3 θ 10 = θ 3 10 = θ −7 = 1 θ 7
  2. z 2 z z 4 = z 2 + 1 z 4 = z 3 z 4 = z 3 4 = z −1 = 1 z
  3. ( −5 t 3 ) 4 ( −5 t 3 ) 8 = ( −5 t 3 ) 4 8 = ( −5 t 3 ) −4 = 1 ( −5 t 3 ) 4
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

what is the function of sine with respect of cosine , graphically
Karl Reply
tangent bruh
Steve
cosx.cos2x.cos4x.cos8x
Aashish Reply
sinx sin2x is linearly dependent
cr Reply
what is a reciprocal
Ajibola Reply
The reciprocal of a number is 1 divided by a number. eg the reciprocal of 10 is 1/10 which is 0.1
Shemmy
 Reciprocal is a pair of numbers that, when multiplied together, equal to 1. Example; the reciprocal of 3 is ⅓, because 3 multiplied by ⅓ is equal to 1
Jeza
each term in a sequence below is five times the previous term what is the eighth term in the sequence
Funmilola Reply
I don't understand how radicals works pls
Kenny Reply
How look for the general solution of a trig function
collins Reply
stock therom F=(x2+y2) i-2xy J jaha x=a y=o y=b
Saurabh Reply
sinx sin2x is linearly dependent
cr
root under 3-root under 2 by 5 y square
Himanshu Reply
The sum of the first n terms of a certain series is 2^n-1, Show that , this series is Geometric and Find the formula of the n^th
amani Reply
cosA\1+sinA=secA-tanA
Aasik Reply
Wrong question
Saad
why two x + seven is equal to nineteen.
Kingsley Reply
The numbers cannot be combined with the x
Othman
2x + 7 =19
humberto
2x +7=19. 2x=19 - 7 2x=12 x=6
Yvonne
because x is 6
SAIDI
what is the best practice that will address the issue on this topic? anyone who can help me. i'm working on my action research.
Melanie Reply
simplify each radical by removing as many factors as possible (a) √75
Jason Reply
how is infinity bidder from undefined?
Karl Reply
Practice Key Terms 1

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask